THE EFFECTIVENESS OF NUTRITION EDUCATION ON INCREASING KNOWLEDGE OF THE PROSPECTIVE BRIDE - Tria Ningsih; Arfah Husna (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Stunting is a health problem that must be considered and treated early because it has a very long impact on a person's life. Aceh province is one of the provinces with the highest stunting prevalence in Indonesia, which is 37.1%. And the prevalence of stunting in West Aceh from 2015 to 2018 increased from 36.3% to 37.0%. This high prevalence is certainly a public health problem that is considered serious and must be considered, so that future generations of the nation will no longer experience stunting. Objective: to examine the effectiveness of nutrition education interventions to increase knowledge of prospective brides and grooms. Research method: the design used in this research is Quasi-Experimental with one grub pretest and posttest. The sample in this study amounted to 10 prospective brides. Samples were selected using a consecutive sampling technique. Data were analyzed using univariate and bivariate analysis (Wilcoxon test). Results: Based on the results of the bivariate test, it was found that nutrition education was effective in increasing cathin knowledge (pvalue = 0.005).